PERJANJIAN PEMBORONGAN PEKERJAAN (OUTSOURCING) DALAM HUKUM KETENAGAKERJAAN - Siti Kunarti (Jurnal Dinamika Hukum, 2009)
Arrangement concerning of outsourcing in Law Number 13 Year 2003 concerning Labour, at one side have opened opportunity of new companies appearance which active in service, and on the other side, have enabled companies which have stood to do efficiency through exploiting of service company of outsourcing to product selected service or products which do not in direct corollation to especial business of company. There is no definitive measure him to determine especial as profession and not especial become the reason of justification for entrepreneur to execute outsourcing business regulasi the clearness in execution of harmless outsourcing in job relation. Kata kunci: outsourcing